Konstruksi Nilai Moral Dalam Relasi Hegemoni Pada Novel ‘Usfur Min Al Syarqi Karya Taufiq El Hakim - Faizetul Ukhrawiyah; Siti Aisyah; Zahrotul Firdaus; Sabiqul Mubarak (Dzil Majaz: Journal of Arabic Literature, 2026)
Discourse analysis is a systematic approach to examining language use in texts and contexts in order to uncover the meanings, values, and messages embedded within them. One of the challenges in literary studies is understanding how an author’s writing style conveys moral values and influences readers’ interpretations. This study addresses that issue by analyzing the moral messages presented in the novel Usfur min al-Syarqi and exploring how the author’s distinctive discourse style contributes to the delivery of those values. The purpose of this research is to identify, describe, and interpret the moral values contained in the novel through a discourse analysis perspective. This study employs a descriptive qualitative method based on library research. Data were collected from the novel as the primary source and supported by relevant books, journal articles, and other scholarly references. The techniques used in data collection included intensive reading, observation, and note-taking to identify discourse patterns and moral themes throughout the narrative. The findings reveal that the novel contains various moral values related to humanity, life struggles, social relationships, and spiritual awareness. These messages are conveyed through a compelling storyline, expressive language, and narrative structures influenced by the author’s personal experiences. The analysis also shows that the novel encourages readers to view life as a dynamic process characterized by changing circumstances and emphasizes that material wealth should not be regarded as the ultimate purpose of life. This study contributes to the field of Arabic literary studies by demonstrating the relevance of discourse analysis in uncovering moral dimensions within literary works and providing a deeper understanding of the relationship between language, narrative style, and ethical values.